Strategic Integration of Hydraulic Accumulators: Best Practices - Tašner, Tadej (International Conference Fluid Power 2025: Conference Proceedings, 2025)
Hydraulic accumulators are indispensable in fluid power systems, providing critical functions such as energy storage, pressure holding or stabilization, and load balancing. However, their effectiveness heavily depends on correct application and circuit integration. This paper explores the principles guiding the proper use of hydraulic accumulators, emphasizing selection criteria, sizing, pre-charge pressure considerations, and safety protocols. It presents strategies for incorporating accumulators into hydraulic circuits to achieve specific functional objectives-such as energy storage, load levelling, and response enhancement-while utilizing the accumulator volume as much as possible and avoiding common pitfalls like exceeding pressure ratio, fluid compatibility issues and lifetime limitations. Through analytical modelling and application-based case studies, the paper illustrates how thoughtful accumulator integration can elevate system efficiency, reliability, and longevity. The findings aim to equip engineers with practical guidelines to make accumulators not just an add-on, but a performance enhancing element within their designs.